A systematic review on the integration of universal design in architectural outdoor environments of higher educational institutions - Ramli, Mohamad Redhuan; Mansor, Noranita; Ja'afar, Mohamad Fakri Zaky; Hassan, Mohammad Mujaheed; Ramli, Ishak (Universiti Teknologi MARA, 2023)
Universities are a critical place for preparing humans for their future endeavours because they provide the necessary knowledge and skills for personal and professional growth. However, inadequate accessibility for students with disabilities (SWDs) has hindered them from fully participating in any university programmes that cause of lack connectivity in High Educational Institution (HEI) campuses area. With the growing numbers of SWDs, HEI should be freely access without any discrimination regarding to the physical environment. Therefore, this article will review the current literature on integration of Universal Design (UD) in HEI for the past 15 years. It is thought that the information and knowledge presented in this review can aid higher education institutions in creating a more inclusive environment to support students with disabilities (SWDs) during their campus life. A list of keywords (UD theory and principles, Students with Disabilities, Accessibility in HEI, and Outdoor environments) related to the scope of this research was identified. In the second step, the keyword for studies on Scopus and WoS were searched, and total of 20 papers were reviewed. A themed review was carried out, where 33 sub-themes were identified based on the keywords. The result suggests a new accessibility model for the integration of UD in architectural environments. This study will benefit future researchers that focus on outdoor environment with the integration of UD theory.